Comparison of phenotypic and genotypic methods of detection of two beta-lactam resistance genes in staphylococcus aureus isolates of mastitic milk from Batangas, Philippines. - Tumamac, Gabriel L.; Aquino, Arrol Jan B.; Rovira, Hope G. (2022)
The study was conducted to compare phenotypic and genotypic methods of detection of two beta-lactam resistant genes in Staphylococcus aureus isolates from mastitic milk. Nine (9/92) S. aureus isolates were revived and used. The isolates were subjected to phenotypic prediction of blaZ gene using the penicillin disk diffusion method and nitrocefin test while prediction of mecA gene was observed using the cefoxitin disk diffusion method. Both the penicillin disk diffusion method and nitrocefin test detected three (33.33%) isolates to be producing beta-lactamase while PCR detected two (22.22%) isolates positive for blaZ gene. Kappa coefficient revealed perfect agreement (1.00) between phenotypic methods and substantial agreement (0.7270) between the phenotypic methods and PCR. In the detection of mecA-mediated methicillin resistance, none of the isolates resulted positive for mecA gene for both tests hence, no methicillin-resistant S. aureus (MRSA) was detected. The results of the study show that there are S. aureus isolates from mastitic milk that expresses beta-lactam resistance through beta-lactamase production however, while there was no MRSA detected, the study highly suggests the monitoring of the antimicrobial usage in the farms and their management practices to avoid further development of resistance and possible transfer of resistance from animals to humans and/or humans to animals.
Keywords: Dairy cattle; Methicillin-resistant staphylococcus aureus